2018
DOI: 10.1101/374926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOPS-dependent endosomal fusion required for efficient cytosolic delivery of therapeutic peptides and small proteins

Abstract: Protein therapeutics represent a significant and growing component of the modern pharmacopeia, but their potential to treat human disease is limited because most proteins fail to traffic across biological membranes. Recently, we discovered that cell-permeant miniature proteins (CPMPs) containing a precisely defined, penta-arginine motif traffic readily to the cytosol and nucleus with efficiencies that rival those of hydrocarbon-stapled peptides active in animals and man. Like many cell-penetrating peptides (CP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 122 publications
(132 reference statements)
2
12
0
Order By: Relevance
“…eGFP-hGal3 and -hGal8 lentiviral particles 55 were added to HeLa cells (10% FBS in DMEM, no p/s) plated on eight-well Lab-Tek chambers (Nunc, Thermo Fisher Scientific) at a density of 7 × 10 3 cells/well. After 16 hours, the cells were washed with warm DPBS three times and labeled with DiIC 16 TCO/SiR-Tz or DiIC 16’ TCO/SiR-Tz as described preciously and imaged by confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…eGFP-hGal3 and -hGal8 lentiviral particles 55 were added to HeLa cells (10% FBS in DMEM, no p/s) plated on eight-well Lab-Tek chambers (Nunc, Thermo Fisher Scientific) at a density of 7 × 10 3 cells/well. After 16 hours, the cells were washed with warm DPBS three times and labeled with DiIC 16 TCO/SiR-Tz or DiIC 16’ TCO/SiR-Tz as described preciously and imaged by confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have indicated that late endosomes may serve as a site of endosomal escape. This is the case for the prototyp-ical CPP TAT, arginine-rich miniature proteins, antisense oligonucleotides, and lipoplexes (Appelbaum et al, 2012;Brock et al, 2018;Erazo-Oliveras et al, 2014;Steinauer et al, 2019;Wang et al, 2017;Yang et al, 2010). Notably, late endosomes are also a portal for the cell entry of toxins and viruses, indicating that cell delivery agents may mimic a mechanism of cell entry that biological species have evolved to exploit (Gibert et al, 2000;Helenius, 2018;Patel et al, 2016;Zaitseva et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Zinc-α2-glycoprotein (ZAG) was isolated and purified from human serum for the first time as an unknown soluble protein [1]. It has similar electrophoretic mobility to 2-globulin and contains 18 % carbohydrates [2]. Previous reports proposed that ZAG can be expressed and secreted by white adipose tissue (WAT) and brown adipose tissue (BAT), thus confirming that ZAG is a naturally secreted adipokine [3].…”
Section: Introductionmentioning
confidence: 99%